Ten Frequently Asked Questions for Small Business Start-Ups - Henry M. Cothran; Allen Wysocki; David Mulkey (EDIS)
Every person starting a business will have questions along the way, and as soon as one question is answered another one arises. In fact, several questions may exist at the same time. This fact sheet presents ten questions that encapsulate the most important issues that must be addressed by those interested in starting a business. This is EDIS document FE571, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published September 2005.